Analysis of 44 Vibrio anguillarum genomes reveals high genetic diversity - Hansen,Mie Johanne; Kudirkiene,Egle; Dalsgaard,Inger (PeerJ, 2020)
Vibriosis, a hemorrhagic septicemic disease caused by the bacterium Vibrio anguillarum, is an important bacterial infection in Danish sea-reared rainbow trout. Despite of vaccination, outbreaks still occur, likely because the vaccine is based on V. anguillarum strains from abroad/other hosts than rainbow trout. Information about the genetic diversity of V. anguillarum specifically in Danish rainbow trout, is required to investigate this claim. Consequently, the aim of the present investigation was to sequence and to characterize a collection of 44 V. anguillarum strains obtained primarily from vibriosis outbreaks in Danish rainbow trout. The strains were sequenced, de novo assembled, and the genomes examined for the presence of plasmids, virulence, and acquired antibiotic resistance genes. To investigate the phylogeny, single nucleotide polymorphisms were identified, and the pan-genome was calculated. All strains carried tet(34) encoding tetracycline resistance, and 36 strains also contained qnrVC6 for increased fluoroquinolone/quinolone resistance. But interestingly, all strains were phenotypic sensitive to both oxytetracycline and oxolinic acid. Almost all serotype O1 strains contained a pJM1-like plasmid and nine serotype O2A strains carried the plasmid p15. The distribution of virulence genes was rather similar across the strains, although evident variance among serotypes was observed. Most significant, almost all serotype O2 and O3 strains, as well as the serotype O1 strain without a pJM1-like plasmid, carried genes encoding piscibactin biosynthesis. Hence supporting the hypothesis, that piscibactin plays a crucial role in virulence for pathogenic strains lacking the anguibactin system. The phylogenetic analysis and pan-genome calculations revealed great diversity within V. anguillarum. Serotype O1 strains were in general very similar, whereas considerable variation was found among serotype O2A strains. The great diversity within the V. anguillarum serotype O2A genomes is most likely the reason why vaccines provide good protection from some strains, but not from others. Hopefully, the new genomic data and knowledge provided in this study might help develop an optimized vaccine against V. anguillarum in the future to reduce the use of antibiotics, minimize economic losses and improve the welfare of the fish.
Keywords: Vibrio anguillarum; Genomes; Vibriosis; Virulence factors; Rainbow trout; Plasmids; Acquired antibiotic resistance genes